Measuring policy-driven innovation in energy efficiency - Lisa Nabitz; Patrick Plötz; Sibylle Braungardt; Matthias Reuter (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2016)
Innovation plays a crucial role in the transition towards a sustainable energy system. In order to simultaneously achieve the objectives of sustainability, energy security and competitiveness of the European economy, various energy policies are active. In recent years, the effect of energy policies on both technological and non-organisational innovations has gained interest. However, the complexity of the systems renders it difficult to disentangle the innovation effects of energy and innovation policies. Here, we outline a unifying framework based on the notion of technological innovation systems. It distinguishes between different phases of the innovation process, actors and functions in the innovation systems and allows studying the effects of policies on these in a systematic fashion. We apply our framework to case studies from the field of energy efficiency in industry for a technological and organisational innovation. Our results help to organise previous research findings and to identify gaps for further studies.
urn:nbn:de:0011-n-3939166
Keywords: 330; energy efficiency; innovation; policy measures; technology diffusion